Spectrum of neurological disorders in children: a 5-year review from a single tertiary hospital in Rivers State, Nigeria - Gabriel-Job, Nneka; Frank-Briggs, Angela I. (International Journal of Research in Medical Sciences, 2026)
Background: Neurological disorders in children from developing countries, such as Nigeria, are increasingly varied. Understanding the spectrum of this disorder and having reliable epidemiological data are important for workforce development and instituting preventive modalities to reduce its occurrence. This study aims to examine the patterns and risk factors of neurological disorders among children presenting at the University of Port Harcourt Teaching Hospital (UPTH). Methods: A descriptive study was conducted among children who attended the consultant paediatric clinic (CPC) from January 2020 to December 2024. A retrospective abstraction of patients’ demographic data and clinical information from their hospital records was done. Statistical package for the social sciences (SPSS) version 25 was used for analysis. Results: A total of 30,824 children under 18 years attended the CPC over the five years; 6281 (20.4%) had neurological diseases. Of these, 3844 (61.2%) were males, and 2437 (38.8%) were females, giving a male to female ratio of 1.6:1. Epilepsy was the most common neurological disorder, accounting for 2,135 cases (34.0%), followed by central nervous system (CNS) infections with 1765 (28.1%) and cerebral palsy with 1005 (16.0%) cases. The common risk factors were birth asphyxia (40.3%), CNS infections (30.2%), neonatal jaundice (13.3%), and prematurity (6.3%). Conclusions: The prevalence of neurological disorders is high in our setting; with epilepsy, CNS infections and cerebral palsy as the most common. There is a male preponderance and the risk factors are mostly preventable and requires improving maternal, new-born and child care.